Technology Of Green Pepper Processing For Farmer - JUNIATY TOWAHA; YULIUS FERRY (Puslitbang Perkebunan, 2011)
International markets other product as white pepper and black pepper is also known other products such as green pepper, orange pepper, pepper powder, oleoresin of pepper and pepper oil. Pepper product from Indonesia is still predominantly exported in black and white pepper, while green pepper only a small portion of total exports of Indonesian pepper. Green was more expensive when compared with black pepper and white pepper. The green pepper have comparative superiority than others product, that is special flavour, color and natural appearance, with the result that able to make used of spices and as food garnishing. The technology as easy to adopt by farmers, so the developing a green pepper on the scale of farmer home industry have a good prospects, as well as alternative products that can increase market absorption, this product is also expected to increase the farmers income. Keywords: Technology, processing, green pepper, farmers.